2018
DOI: 10.15561/20755279.2018.0106
|View full text |Cite
|
Sign up to set email alerts
|

The ways of improvement special physical training of high-qualified women volleyball players in competitive period of annual macrocycle

Abstract: to evaluate the influence of creating the program of training process in the competition period of the annual macro cycles on the level of special physical training of women volleyball players. Material: women volleyball players of high qualification participated in the experiment (n=14, age 20-22 years). An assessment of the level of special physical fitness of volleyball players was conducted. It is used author's program. Results: features of the functional dependence of the level of general physical prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Reliable interconnection of the average level between the integral indicator of coordination preparedness and the indicator of proprio-receptive functions can be regarded as a fact of kinesthesia (muscle sensation) significance in the structure of coordination readiness of volleyball players (girls) at the age of 15-17. The results obtained by us confirmed the experimental data of other authors (Ivashchenko et al, 2018;Malikova, Doroshenko, Symonik, Tsarenko, & Veritov, 2018), on the greater kinesthesia significance for females compared to males.…”
Section: Discussionsupporting
confidence: 91%
“…Reliable interconnection of the average level between the integral indicator of coordination preparedness and the indicator of proprio-receptive functions can be regarded as a fact of kinesthesia (muscle sensation) significance in the structure of coordination readiness of volleyball players (girls) at the age of 15-17. The results obtained by us confirmed the experimental data of other authors (Ivashchenko et al, 2018;Malikova, Doroshenko, Symonik, Tsarenko, & Veritov, 2018), on the greater kinesthesia significance for females compared to males.…”
Section: Discussionsupporting
confidence: 91%
“…The meaning of sports injuries is that people in the process of sports, the occurrence of sports-related injuries and injuries. This kind of injury and injury is related to the sports project and has certain technical characteristics [ 7 ]. The injury and injury caused by sports often have a direct or indirect relationship with the characteristics of the sport itself (technology and tactical movements), the behavior of the sports subject (training level), objective conditions (sports environment, equipment, and equipment), and other factors.…”
Section: Related Workmentioning
confidence: 99%
“…Similar processes were recorded in experimental studies of the team of authors (Kumar et al, 2021;Zerf et al, 2019), which show that special exercises are an effective means of developing coordination abilities and contribute to the formation of specialized psychophysiological functions that ensure the effectiveness of the competitive activity in volleyball. Based on the study of special literature and the results of their own studies, researchers summarized the ways of improving the special physical training of highlyskilled volleyball players in the preparatory (Trajkovic et al, 2012) and competitive periods (Malikova et al, 2018) of the annual macrocycle and showed their role in achieving a steady effect for maximum fulfilment of female athletes' technical and tactical potential in the competitive process.…”
Section: Introductionmentioning
confidence: 99%